Determining Mango Plant Types Using YOLOv4 - Prya Artha Widjaja; Jose Ryu Leonesta (PT FORMOSA CENDEKIA GLOBAL, 2022)
Mango plants consist of many types. This study tries to use leaf imagery to determine the type of mango plant. In this study, one of the object recognition methods in Deep Learning was used, namely YOLO (You Only Look Once) version 4. The types of mango used were manalagi, apple, golek and sweet and fragrant. The study used 457 pieces of data for model training and yielded an accuracy of around 95 percent.